A Study on the Interaction Between Intestinal Microbiota, Inflammatory Cytokines, and the Expression of miR-330-3p and miR-515-5p in Patients with Ulcerative Colitis - Qin, Kaidi; Hu, Chao; Li, Wenjun; Wang, Wulin; Zhang, zilong (Journal of Medical Biochemistry, 2025)
Background: Ulcerative colitis (UC) has a complex pathogenesis involving multiple factors. This study aims to explore the interplay among intestinal microbiota, serum inflammatory cytokines, and miR-330-3p, miR-515-5p in UC patients for novel treatment strategies. Methods: The study enrolled 95 healthy controls, 88 UC patients in remission, and 91 in active diseases. Assessments included clinical data, intestinal microbiota detection (using culture methods), serum cytokine measurement (using ELISA assay), and miRNA expression analysis (using RT-qPCR). ROC curves evaluated diagnostic value, and multivariate logistic regression identified risk factors. Results: From the control group to UC remission, and then to seizure UC, significant decreases were observed in Bifidobacterium, Lactobacillus counts, IL-10 levels, and miR-515-5p expression, while increases were noted in Enterobacteriaceae, Enterococcus counts, IL-6, TNF-α levels, and miR-330-3p expression (P 0.5, p
Keywords: Ulcerative colitis; intestinal microbiota; inflammatory cytokines; miR-330-3p; miR-515-5p